Is There Correlation Between Students’ Memorizing Quran and Their Mathematics Score? Study on Islamic Boarding Senior High School - Rambe, Dini Savitri; Siregar, Rama Nida (IKIP Siliwangi, 2025)
This study was motivated by the observation of varying academic performance in integral mathematics among students with different levels of Quran memorization at Darul Mursyidi Islamic Boarding School, Sialogo. Integrating religious and academic education is a key concern in Islamic institutions, raising the question of whether memorizing the Quran can influence cognitive and analytical skills, particularly in mathematics. The aim of this research is to examine whether there is a significant relationship between Quran memorization and academic achievement in integral mathematics. This quantitative study involved 20 eleventh-grade students from Madrasah Aliyah. Data were collected through a written mathematics test focusing on integral material and Quran memorization scores sourced from the Tahfidz instructor. The correlation between these two variables was analyzed using the Pearson product-moment correlation formula. The findings reveal a strong and positive correlation between students' Quran memorization and their performance in integral mathematics, indicating that students who had higher memorization scores tended to achieve better results in mathematics. Furthermore, students with strong memorization abilities also demonstrated better logical thinking and responsiveness, not only in math but also in subjects such as science, fiqh, and faraid. These results support the view that memorizing the Quran can enhance students’ cognitive functions, including memory and reasoning, which are essential for learning mathematics. The study concludes that integrating Quran memorization into the educational process may serve as a beneficial strategy for improving students' academic outcomes.